Use of polyester-resin composite fibers for reinforcing concrete

By using polyester-resin composite fibers, using vacuum degassing, impregnating resin, shaping and ultraviolet polymerization, the shortcomings of concrete in tensile strength and crack resistance are solved, and the uniform distribution of fibers in concrete is achieved and The improvement of high mechanical performance while reducing CO2 emissions.

CN119403666APending Publication Date: 2025-02-07MICHELIN & CO (CIE GEN DES ESTAB MICHELIN)
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380046978.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-15
Filing Date
2023-06-14
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing concrete has shortcomings in tensile strength and crack resistance, and the metal fibers used are prone to sink and corrosion, and the mechanical strength and use temperature of the synthetic fibers are not as good as that of the metal fibers.

Method used

Using polyester-resin composite fibers, a high mechanical properties and corrosion resistance are prepared by degassing in a vacuum chamber, impregnating resin in an impregnation chamber, shaping in a shaping mold, polymerizing and cutting in an ultraviolet irradiation chamber. Polyester-resin composite monofilament.

Benefits of technology

The uniform distribution of fibers in concrete is achieved, the tensile strength and crack resistance of concrete are improved, and CO2 emissions are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119403666A_ABST
    Figure CN119403666A_ABST
Patent Text Reader

Abstract

The invention relates to a monofilament made of a polyester-resin composite material comprising polyester threads embedded in a crosslinked resin, said monofilament having a length in the range of 5 mm to 85 mm, a diameter in the range of 0.2 mm to 1.3 mm and a porosity of less than 2%, and to the use thereof for reinforcing concrete. The invention also relates to a concrete comprising said monofilament and to a method for obtaining said monofilament.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a polyester-resin composite fiber for reinforcing concrete and a method for obtaining the polyester-resin composite fiber. Background Art

[0002] Concrete is arguably the most widely used building material today due to its high compressive strength, durability, longevity and resilience. Its properties make it the material of choice, especially in the fields of buildings, roads and engineering structures.

[0003] Concrete consists essentially of aggregates held together by a binder, most commonly Portland cement. To improve the properties of concrete, it is known to use additives such as ultrafine particles (e.g. silica fume), superplasticizers (also known as water-reducing plasticizers) or metal, synthetic or mineral fibers.

[0004] Although very resistant to compression, concrete has low tensile strength and tension is often accompanied by the appearance of cracks. To overcome this problem, it is known to use reinforcing fibers. Due to their mechanical properties, metal fibers are particularly useful for reinforcing concrete. Therefore, they are very widely used to make concrete more ductile and improve its resistance to cracking.

[0005] However, metal fibers have the disadvantage of being sensitive to corrosion, which can be detrimental to the life of the concrete comprising such fibers. In addition, their density is generally greater than 7.7 and therefore they cannot be evenly distributed in concrete with a lower density (metal fibers tend to sink under the effect of gravity, or even under the effect of vibration when the concrete is vibrated to remove any air bubbles that may have formed during the pouring process).

[0006] To address this problem, it has been proposed to use synthetic fibers instead of metal fibers. However, the mechanical strength of these fibers (e.g. elastic (Young's) modulus, tensile strength) is not as good as that of metal fibers. In addition, their use temperature (usually between 100°C and 160°C) is much lower than that of metal fibers (approximately between 600°C and 900°C), which may limit their use in certain applications.

[0007] Therefore, it would still be advantageous to have fibers that are corrosion resistant (to increase the service life of the concrete) and have improved mechanical properties (to improve crack resistance) compared to current non-metallic fibers. Summary of the invention

[0008] In conducting research, the present applicant has surprisingly found that the above-mentioned problems can be solved by using specific polyester-resin composite fibers.

[0009] The Applicant has also observed many advantages obtained with the fibres according to the invention. Compared with the fibres of the concrete of the prior art, they are very easy to implement, in particular in the stage of mixing the various components of the concrete (easy dispersion), and in the stage of drying the concrete: since their density is close to that of the concrete, the fibres remain uniformly distributed in the concrete (they do not tend to sink like metal fibres whose density is greater than that of the concrete, nor to rise like synthetic fibres whose density is less than that of the concrete). The fibres of the invention also have a much higher maximum temperature of use than the synthetic fibres currently used. Moreover, and more generally, the use of the fibres according to the invention, due to their density and their reinforcing capacity, makes it possible, for the same reinforcing level, to reduce the overall emissions of CO2 considerably compared with the use of other fibres of the prior art.

[0010] Therefore, the present invention relates to a polyester-resin composite monofilament comprising a polyester filament embedded in a cross-linked resin, having a length in the range of 5 mm to 85 mm and a diameter in the range of 0.2 mm to 1.3 mm, and characterized in that the porosity of the monofilament is less than 2%.

[0011] The present invention also relates to the use of at least one monofilament according to the present invention for reinforcing concrete and / or reducing the weight of concrete and / or reducing or preventing cracking of concrete, and to concrete comprising a plurality of monofilaments cut according to the present invention, the volume ratio of the monofilaments in the concrete preferably being in the range of 0.1% to 6%.

[0012] The present invention also relates to a method for manufacturing a polyester-resin composite monofilament comprising a polyester filament embedded in a cross-linked resin, the method comprising the following consecutive steps:

[0013] - forming a linear arrangement of polyester filaments and conveying this arrangement in the feed direction,

[0014] - degassing the polyester threads of the arrangement by the action of a vacuum in a vacuum chamber,

[0015] - at the outlet of the vacuum chamber, after degassing, passing through an impregnation chamber under vacuum to impregnate the arranged polyester filaments with a photocurable resin composition in a liquid state (referred to as "impregnation resin"), thereby obtaining a prepreg comprising the polyester filaments and the resin composition,

[0016] - passing the prepreg through a shaping die having a cross-section with a predetermined area and shape so as to give it a monofilament shape,

[0017] - Downstream of the die, the resin composition is polymerized under the action of ultraviolet rays in a UV irradiation chamber, the irradiation chamber comprising a tube transparent to ultraviolet rays (referred to as an irradiation tube), through which the monofilaments to be formed are passed and through which a stream of inert gas flows, the running speed of the monofilaments through the irradiation chamber (denoted as V ir ) is greater than 50m / min, the irradiation time of the monofilament in the irradiation chamber (expressed as D ir ) is equal to or greater than 1.5s,

[0018] - The monofilaments are cut into lengths ranging from 5 mm to 85 mm.

[0019] I-Definition

[0020] In the present application, unless expressly stated otherwise, all percentages (%) shown are percentages (%) by weight.

[0021] The expression "composition based on" is understood to mean that the composition comprises a mixture and / or in situ reaction products of the various components used, some of which are able and / or intended to react at least partially with one another during the various stages of manufacture of the composition; the composition may therefore be in a completely or partially crosslinked state, or in a non-crosslinked state.

[0022] In addition, any numerical interval represented by the expression "between a and b" means a numerical range extending from greater than a to less than b (i.e., excluding the end values ​​a and b), while any numerical interval represented by the expression "a to b" means a numerical range extending from a to b (i.e., including the strict end values ​​a and b). In the present application, when a numerical interval is represented by the expression "a to b", it is also preferably intended to represent the interval represented by the expression "between a and b".

[0023] All values ​​of the glass transition temperature "Tg" described herein are measured in a known manner by DSC (Differential Scanning Calorimetry) according to Standard ASTM D3418 (1999). BRIEF DESCRIPTION OF THE DRAWINGS

[0024] II-Brief description of the drawings

[0025] [ Figure 1 ] Figure 1 is a schematic diagram of a method for synthesizing a monofilament according to the present invention before the monofilament is cut to a given length.

[0026] [ Figure 2 ] Figure 2 (For ease of understanding, it is not shown to scale) is a diagram showing a cross section of a monofilament according to the present invention. DETAILED DESCRIPTION

[0027] III-Description of the Invention

[0028] The present invention therefore relates to a monofilament (or fiber, both terms may be used in an equivalent manner) made of a polyester-resin composite material (abbreviated as "CPR"), comprising polyester filaments embedded in a cross-linked resin (i.e. a resin that solidifies after cross-linking), having a length in the range of 5 mm to 85 mm and a diameter in the range of 0.2 mm to 1.3 mm, and characterized in that the porosity of the monofilament is less than 2%.

[0029] "Polyester yarn" means a yarn of linear macromolecules formed by groups linked together by ester bonds. Polyesters are produced by polycondensation carried out by esterification reaction between a dicarboxylic acid or one of its derivatives and a diol. For example, polyethylene terephthalate can be produced by polycondensation of terephthalic acid and ethylene glycol. Among the known polyesters, mention may be made of polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polybutylene terephthalate (PBT), polybutylene naphthalate (PBN), polytrimethylene terephthalate (PPT) or polytrimethylene naphthalate (PPN).

[0030] Preferably, the polyester thread is a thread selected from polyethylene terephthalate (PET) and polyethylene naphthalate (PEN), preferably completely made of polyethylene terephthalate (PET).

[0031] As examples of polyester fibers that can be used in the context of the present invention, mention may be made of the PET fibers sold under the name “PET HMLS 334TEX HSP40” by the company Hyosung or under the name “1X50-3340-892-00” by the company Glanzstoff Longlaville.

[0032] Typically, polyester filaments (preferably PET filaments) exist in the form of single multifilament fibers or multiple multifilament fibers combined together. In the case of multiple multifilament fibers combined together, the multifilament fibers are preferably substantially unidirectional. Each multifilament fiber can include tens, hundreds or even thousands of independent polyester (preferably PET) filaments. The average diameter of these extremely fine independent filaments is typically and preferably 15 μm to 35 μm, more preferably 15 μm to 25 μm. The cross section of the independent filaments is preferably cylindrical.

[0033] Preferably, in the CPR monofilament of the present invention, the filaments of the monofilament are substantially parallel to each other. In particular, the degree of alignment of the polyester filaments preferably satisfies that more than 85% (number %) of the filaments have an inclination of less than 2.0 degrees, more preferably less than 1.5 degrees relative to the axis of the monofilament, the inclination (or misalignment) being measured as described in the above disclosure of Thompson et al. It is also preferred that the CPR monofilament according to the present invention has no helical deformation, i.e. it is not twisted. In any case, the number of turns per meter of the CPR monofilament is less than 5, preferably less than 2, preferably less than 0.5, preferably 0 to 0.5.

[0034] Preferably, the weight content of polyester fibers (ie filaments) in the CPR monofilament is in the range of 20% to 60%, preferably 25% to 40%.

[0035] This weight content of polyester fibers is calculated using the ratio of the count of the initial polyester fibers to the count of the final CPR monofilament. The count (or linear density) is determined on at least three samples (each sample corresponds to a length of 50 m) by weighing the length; the count is given in tex (weight in grams of 1000 m of product - as a reminder, 0.111 tex is equal to 1 denier).

[0036] Furthermore, the volume fraction of the polyester fibers in the CPR monofilament is advantageously in the range of 20% to 50%, preferably 20% to 30%.

[0037] The volume fraction of polyester fiber in the final CPR monofilament corresponds to the surface fraction of the polyester fiber of the cross section of the CPR monofilament relative to the total area of ​​the cross section of the CPR monofilament. The surface fraction of the polyester fiber can be determined in the same manner as described below for measuring porosity.

[0038] Furthermore, the cross-linked resin accounts for 40% to 80% by weight, preferably 60% to 75% by weight of the CPR monofilament of the present invention. Furthermore, the volume fraction of the resin in the CPR monofilament is advantageously in the range of 50% to 80%, preferably 70% to 80%. The weight percentage and volume fraction of the cross-linked resin can be obtained according to a method similar to that used to obtain the weight content and volume fraction of the above-mentioned polyester fiber.

[0039] By definition, the resins used are crosslinkable (ie curable) resins which can be crosslinked (cured) by any known method, in particular and preferably by UV (or UV-visible) radiation, preferably emitting in the spectrum ranging at least from 300 nm to 450 nm.

[0040] Here, the term "resin" or "resin composition" is understood to mean a resin in unmodified form, or any composition based on this resin and comprising at least one additive (i.e. one or more additives) before crosslinking. The term "crosslinked" resin is naturally intended to mean a resin that is cured (light-cured and / or heat-cured) in a state characteristic of "thermosetting" polymers (unlike "thermoplastic" polymers), in other words, in the form of a three-dimensional bond network.

[0041] Advantageously, the crosslinking resin is based at least on:

[0042] - a crosslinkable resin selected from the group consisting of vinyl ester resins (preferably urethane vinyl ester resins), epoxy resins, polyester resins and mixtures thereof,

[0043] - a cross-linking system, preferably comprising a photoinitiator, which is reactive to UV radiation above 300 nm.

[0044] As crosslinkable resins, polyester resins or vinyl ester resins are preferably used, more preferably vinyl ester resins. "Polyester" resins are understood in a known manner to mean resins of the unsaturated polyester type. As for the vinyl ester resins, they are well known in the field of composite materials.

[0045] Without this definition being limiting, the vinyl ester resin is preferably of the epoxy vinyl ester type. More preferably, use is made of vinyl ester resins (especially of the epoxy type) based at least in part on phenolic resins (also called phenolics) and / or bisphenols (i.e. grafted onto structures of this type), i.e. preferably vinyl ester resins based on phenolic resins, bisphenols or phenolic resins and bisphenols.

[0046] Preferably, the initial tensile modulus of the resin measured at 23°C is greater than 3.0 GPa, more preferably greater than 3.5 GPa.

[0047] Epoxy vinyl ester resins based on phenolic resins (the part between square brackets in the following formula I) correspond, for example, in a known manner to the following formula (I):

[0048]

[0049] Epoxy vinyl ester resins based on bisphenol A (the part between square brackets in the following formula (II)) ("A" serves to indicate that the product is prepared using acetone) correspond, for example, to the following formula:

[0050]

[0051] Epoxy vinyl ester resins of the phenolic and bisphenol type show excellent results. As examples of such resins, mention may in particular be made of the vinyl ester resins "ATLAC 590" and "ATLAC E-Nova FW 2045" from the company AOC described in the above-mentioned patent applications EP-A-1074369 and EP-A-1174250 (diluted with about 40% styrene). Epoxy vinyl ester resins are available from other manufacturers, for example AOC (USA - "Vipel" resins).

[0052] The crosslinking system for the impregnating resin (resin composition) preferably comprises a photoinitiator, said photoinitiator being sensitive (reactive) to UV radiation above 300 nm, preferably between 300 nm and 450 nm. The photoinitiator is used in a preferred content of 0.5% to 3%, more preferably 1% to 2.5%. Preferably, the resin crosslinking system also comprises a crosslinking agent, for example a crosslinking agent in a content of between 5% and 15% (% by weight of the impregnating composition), said crosslinking agent being as defined above.

[0053] Preferably, the photoinitiator is from the family of phosphine compounds, more preferably a bis(acyl)phosphine oxide (e.g. bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide (“Omnirad 819” from IGM or “SpeedCure BPO” from Lambson)), or a mono(acyl)phosphine oxide (e.g. “Esacure TPO” from IGM), which phosphine compounds can be mixed with other photoinitiators, such as α-hydroxyketone type photoinitiators (e.g. dimethylhydroxyacetophenone (e.g. “Omnirad 1173” from IGM) or 1-hydroxycyclohexylphenyl ketone (e.g. “Omnirad 184” from IGM)), benzophenones (e.g. 2,4,6-trimethylbenzophenone (e.g. “Esacure TZT” from IGM)) and / or thioxanthone derivatives (e.g. isopropylthioxanthone (e.g. “Esacure Omnirad ITX” from IGM)).

[0054] The crosslinking agent is preferably selected from the family of triacrylates.

[0055] The diameter D of the CPR monofilament of the present invention is preferably in the range of 0.2 mm to 1.3 mm, preferably between 0.25 mm and 1.25 mm, more preferably between 0.3 mm and 1.2 mm, in particular between 0.4 mm and 1.1 mm.

[0056] This definition covers both substantially cylindrical (with a circular cross section) monofilaments and monofilaments of other shapes, such as elliptical monofilaments (with a more or less flat shape) or monofilaments with a rectangular cross section. In the case of non-circular cross sections, unless otherwise specifically stated, by convention D is the diameter known as the gap diameter, i.e. the diameter of an imaginary cylinder of revolution around the monofilament, in other words the diameter of the circumscribed circle around its cross section.

[0057] In addition, the length L of the CPR monofilament of the present invention is preferably in the range of 10 mm to 80 mm, for example, 15 mm to 60 mm. In this case, the length / diameter ratio L / D of the CPR monofilament of the present invention is advantageously in the range of 10 to 110, preferably 20 to 90, preferably 25 to 80, preferably 30 to 70.

[0058] According to the invention, the porosity of the CPR monofilament is advantageously less than 1%, preferably less than 0.5%. Advantageously, the porosity of the CPR monofilament is between 0% and 2%, preferably between 0.01% and 1%, preferably between 0.05% and 0.5%.

[0059] The porosity can be measured by microscopy (e.g., scanning electron microscopy), preferably using area calculation software, such as the FIJI program. To perform the measurement, the following protocol is preferably performed:

[0060] - Obtain cross-linked CPR monofilaments,

[0061] - coating it with a cold coating resin, for example of the epoxy type, for example in a vacuum coating device (for example the CitoVac from the company Stuers),

[0062] - cutting the coated CPR monofilament, for example using a hydraulic shear (for example "SH-5214" from the company Baileigh),

[0063] - polishing the cross section of the CPR monofilament, for example using a mechanical polisher such as from the company Mecapol, preferably to a final particle surface of 0.25 μm,

[0064] - Apply 1 nm to 4 nm of gold, for example using a gold sputter coater (e.g. from the company Cressington coater of series 108 or 208),

[0065] - Observe the cross section of the CPR filament using a (15 kV) scanning electron microscope, preferably under vacuum, and

[0066] - Calculate the surface area percentage of porosity using an image processing program (eg FIJI). "Porosity" of a CPR monofilament refers to any gas (particularly air) or void space present within the CPR monofilament.

[0067] According to the present invention, the breaking stress Cr of the CPR monofilament is advantageously greater than 300 MPa, more preferably greater than or equal to 320 MPa. In particular, the breaking stress of the monofilament is preferably between 300 MPa and 500 MPa, preferably 320 MPa to 470 MPa.

[0068] Advantageously, the initial tensile modulus (expressed as E 23 ) (also called Young's modulus) is greater than 4 GPa, preferably greater than 4.5 GPa. In particular, the E 23 Preferably between 4 GPa and 8 GPa, preferably between 4.5 GPa and 7 GPa.

[0069] Mechanical tensile properties of CPR monofilament (modulus E 23 , breaking stress Cr and breaking elongation Ar) can be measured in a known manner according to the protocol described in Section IV-1 below.

[0070] The glass transition temperature (expressed as Tg) of the crosslinked resin is preferably greater than 190° C., preferably greater than 195° C., in particular greater than 200° C. In the present application, unless otherwise specifically stated, the glass transition temperature is measured in a known manner, for example by DSC (Differential Scanning Calorimetry) in the second scan according to standard ASTM D3418 of 1999 (DSC apparatus "822-2" from Mettler Toledo; nitrogen atmosphere; the sample is first raised from ambient temperature (23° C.) to 250° C. (10° C. / min), then rapidly cooled to 23° C., and then finally the DSC curve is recorded with a gradient of 10° C. / min from 23° C. to 250° C.).

[0071] Preferably, the density (or mass per unit volume, in g / cm 3 The density is measured by a professional "PG503 DeltaRange" balance from the company Mettler Toledo (at 23° C.); several centimeters of the sample are weighed in turn in air and immersed in ethanol, and the device's software then determines the average density from three measurements.

[0072] The present invention also relates to a method for manufacturing a monofilament (or fiber, both terms may be used in an equivalent manner) made of a polyester-resin composite material (abbreviated as "CPR"), said method comprising the following consecutive steps:

[0073] - forming a linear arrangement of polyester filaments and conveying this arrangement in the feed direction,

[0074] - degassing the polyester threads of the arrangement by the action of a vacuum in a vacuum chamber,

[0075] - at the outlet of the vacuum chamber, after degassing, passing through an impregnation chamber under vacuum to impregnate the arranged polyester filaments with a photocurable resin composition in a liquid state (referred to as "impregnation resin"), thereby obtaining a prepreg comprising the polyester filaments and the resin composition,

[0076] - passing the prepreg through a shaping die having a cross-section with a predetermined area and shape so as to give it a monofilament shape,

[0077] - Downstream of the die, the resin composition is polymerized under the action of ultraviolet rays in a UV irradiation chamber, the irradiation chamber comprising a tube transparent to ultraviolet rays (referred to as an irradiation tube), through which the monofilaments to be formed are passed and through which a stream of inert gas flows, the running speed of the monofilaments through the irradiation chamber (denoted as V ir ) is greater than 50m / min, the irradiation time of the monofilament in the irradiation chamber (expressed as D ir ) is equal to or greater than 1.5 s, at the end of which a CPR monofilament comprising a polyester filament embedded in a cross-linked resin is obtained,

[0078] - Cutting the monofilaments into lengths ranging from 5 mm to 85 mm, at the end of which step, CPR monofilaments according to the invention comprising polyester filaments embedded in a cross-linking resin are obtained.

[0079] All the steps of the process of the invention (arranging, degassing, impregnation, shaping, polymerization, winding (where applicable) and cutting) are independently of one another known to the person skilled in the art, as are the materials used (multifilament fibers and resin composition); for example, they are described in either or both of the patent applications EP-A-1074369 and EP-A-1174250.

[0080] According to the invention, it will be recalled in particular that, before any impregnation of the fibers, an essential step of degassing the arranged fibers by the action of a vacuum must be carried out, in order in particular to improve the effectiveness of the subsequent impregnation and in particular to ensure the absence of air bubbles in the final composite monofilament.

[0081] After passing through the vacuum chamber, the polyester filaments enter an impregnation chamber which is completely filled with impregnation resin and is therefore free of air: in this sense, this impregnation step may be referred to as "impregnation under vacuum".

[0082] The mould, known as a “shaping” mould, is able to adjust the proportion of resin to polyester fibres (preferably PET fibres) by having a cross section of a given size (usually and preferably circular or rectangular), while giving the prepreg the desired shape and thickness of the monofilament.

[0083] Advantageously, the diameter of the monofilaments leaving the shaping die ranges from 0.2 mm to 1.3 mm, preferably from 0.25 mm to 1.25 mm, preferably from 0.3 mm to 1.2 mm.

[0084] The polymerization or UV irradiation chamber then has the function of polymerizing or cross-linking the resin under the action of UV radiation.

[0085] The UV irradiation chamber includes one or more UV irradiators (or radiators). Advantageously, the irradiation chamber includes a plurality of UV irradiators arranged in a row around the irradiation tube, i.e., at least two (two or more than two) UV irradiators. Each UV irradiator generally includes one (at least one) UV lamp (preferably emitting in a spectrum of 200nm to 600nm) and a parabolic reflector, the focus of the parabolic reflector being the center of the irradiation tube; the linear power density provided is preferably between 2000 watts / m and 14000 watts / m. Still more preferably, the irradiation chamber includes at least three, in particular at least four rows of UV irradiators.

[0086] Even more preferably, the linear power density provided by each UV irradiator is between 2500 Watt / m and 12000 Watt / m, in particular in the range of 3000 Watt / m to 10000 Watt / m.

[0087] UV irradiators suitable for the method according to the invention are known to the person skilled in the art and are available, for example, from the company Dr. UV radiators equipped with "UVAPRINT" lamps (iron-doped high-pressure mercury lamps) are sold by AG (Germany) under the reference "1055LCP AM UK". The nominal (maximum) power of each radiator of this type is equal to about 13,000 Watts, the power output being adjustable in practice by means of a potentiometer between 30% and 100% of the nominal power.

[0088] The diameter of the irradiation tube (preferably made of glass) is preferably between 10 mm and 80 mm, more preferably between 20 mm and 60 mm.

[0089] Between the shaping die and the final receiving support, the tension to which the polyester fibers are subjected is preferably maintained at a moderate level, preferably between 0.2 cN / tex and 2.0 cN / tex, more preferably between 0.3 cN / tex and 1.5 cN / tex; in order to control this, these tensions can be measured directly at the exit of the irradiation chamber, for example by means of a suitable tensiometer known to those skilled in the art.

[0090] The final CPR monofilament thus formed by passing through the UV irradiation chamber (where the resin is now in a solid state) is then recovered, for example on a take-up drum, where it can be wound up to a very long length. Thus, the method may include a winding step for storing the monofilament after it has passed through the UV irradiation chamber.

[0091] The monofilaments can be cut so as to obtain monofilaments having a length in the range of 5 mm to 85 mm, preferably 10 mm to 80 mm, preferably 15 mm to 60 mm. In this case, the length / diameter ratio of the monofilaments is advantageously in the range of 10 to 110, preferably 20 to 90, preferably 25 to 80, preferably 30 to 70.

[0092] Particularly advantageously, the method of the present invention for manufacturing a CPR monofilament comprises the following essential steps:

[0093] - The running speed of the monofilament through the irradiation chamber (V ir ) greater than 50m / min;

[0094] - The running time of the monofilament through the irradiation chamber (D ir ) is equal to or greater than 1.5s and equal to or less than 10s;

[0095] The irradiation chamber comprises a tube transparent to UV rays (for example a quartz tube or preferably a glass tube), called the irradiation tube, through which the monofilament moves during the formation process, and through which flows a stream of an inert gas (preferably nitrogen).

[0096] These combined steps enable the preferred improved properties of the CPR monofilaments of the present invention to be achieved, namely, in particular, improved Tg, elongation Ar and modulus (E and E') properties.

[0097] In particular, in the case where no inert gas (eg nitrogen) purging is used in the irradiation tube, it is observed that the above-mentioned properties of the CPR monofilament deteriorate very rapidly during the manufacturing process, so that industrial performance can no longer be guaranteed.

[0098] In addition, if the irradiation time D of the monofilament in the irradiation chamber is ir If the irradiation time D of the monofilament in the irradiation chamber is too short (less than 1.5 s), many tests show that the resin is not fully cross-linked, resulting in poor mechanical properties (including breaking stress and flexural strength).ir Too long (eg greater than 10 s) and this increases the risk of the resin boiling, thereby creating more voids and compromising mechanical properties (including fracture stress).

[0099] It is thus understood that, thanks to the combination of the steps of the method according to the invention, in particular thanks to the step of degassing the arranged polyester threads by the action of a vacuum in a vacuum chamber and the step of irradiating the polyester threads in a tube through which a flow of inert gas passes at the above speed V ir and the above irradiation time D ir The step of polymerization was performed to obtain a CPR monofilament with a porosity of less than 2% and a breaking stress of more than 300 MPa.

[0100] It is also observed that high irradiation speed V ir (greater than 50 m / min, preferably between 50 m / min and 150 m / min) is beneficial on the one hand to an excellent degree of alignment of the polyester filaments within the CPR monofilament and on the other hand to better maintenance of the vacuum in the vacuum chamber, thereby significantly reducing the risk of a certain amount of impregnation resin migrating back from the impregnation chamber into the vacuum chamber and therefore to a better impregnation quality.

[0101] Preferably, the speed V ir Between 50 m / min and 150 m / min, more preferably in the range of 60 m / min to 120 m / min.

[0102] Preferably, the irradiation time D ir Between 1.5 s and 10 s, more preferably in the range of 2 s to 5 s.

[0103] One subject matter described herein is a CPR monofilament obtainable by a method according to the invention, preferably according to said method:

[0104] - The running speed of the monofilament through the irradiation chamber (V ir ) greater than 50m / min;

[0105] - The running time of the monofilament through the irradiation chamber (D ir ) is equal to or greater than 1.5s and equal to or less than 10s;

[0106] the irradiation chamber comprises a tube transparent to UV rays (for example a quartz tube or preferably a glass tube), called the irradiation tube, through which the monofilament moves during the formation process, through which a stream of inert gas (preferably nitrogen) flows,

[0107] - the length of the CPR monofilament ranges from 5 mm to 85 mm, preferably from 10 mm to 80 mm, preferably from 15 mm to 60 mm,

[0108] - The diameter of the CPR monofilament ranges from 0.2 mm to 1.3 mm, preferably from 0.25 mm to 1.25 mm, preferably from 0.3 mm to 1.2 mm.

[0109] Thus, the CPR monofilaments obtainable by the method according to the invention comprise polyester filaments (preferably PET filaments) impregnated in a cross-linked resin, having a length ranging from 5 mm to 85 mm, a diameter ranging from 0.2 mm to 1.3 mm and a porosity of less than 2%. All the above characteristics of the monofilaments according to the invention also apply to the monofilaments obtainable by the method according to the invention. In particular, taking into account the specific steps of the method according to the invention, the monofilaments advantageously have a porosity of less than 1%, preferably less than 0.5%, and / or a breaking stress greater than 300 MPa, preferably greater than or equal to 320 MPa, and / or an initial tensile modulus of the monofilament measured at 23° C. (expressed as E ) greater than 4 GPa, preferably greater than 4.5 GPa. 23 ).

[0110] The invention also relates to a tow comprising a plurality of CPR monofilaments according to the invention (or CPR monofilaments obtainable by a method according to the invention) and at least one element for holding the cut monofilaments together. Preferably, the holding element is a rupturable film, such as a tearable, dispersible water-soluble film. Preferably, at least one holding element is a water-soluble thread.

[0111] Advantageously, the retaining element is a water soluble film, preferably made of a material selected from polyvinyl alcohol (PVA) or any water soluble or bioplastic polymer, such as a bioplastic derived from milk casein.Preferably, at least one water soluble film is made of a material selected from polyvinyl alcohol.

[0112] The tow according to the invention advantageously comprises a number of cut filaments in the range of 300 to 20,000.

[0113] The monofilaments constituting the tow may have the same or different sizes. For example, the tow may include monofilaments having different lengths, diameters and / or length-to-diameter ratios. Advantageously, the tow includes monofilaments according to the invention whose lengths and diameters differ from each other by no more than 10%, preferably by no more than 3%.

[0114] As mentioned above, the monofilaments according to the invention can be used in particular as an additive to concrete. Therefore, the present invention also relates to the use of at least one CPR monofilament according to the invention (or a CPR monofilament obtainable by a method according to the invention) or a tow according to the invention for reinforcing concrete and / or reducing the weight of concrete and / or reducing or preventing cracking of concrete.

[0115] The invention also relates to a concrete comprising a plurality of cut CPR monofilaments according to the invention (or CPR monofilaments obtainable by the method according to the invention). The concrete can be prepared by any technique known to a person skilled in the art.

[0116] Advantageously, the volume proportion of the monofilaments according to the invention in the concrete according to the invention is in the range from 0.1% to 6%, for example from 0.1% to 1.5% for "conventional" concrete (for example of type BPS C40 / 50XA3), or from 1.5% to 6% for ultra-high performance fiber reinforced concrete (UHPFRC).

[0117] An example of the manufacture of a CPR monofilament according to the invention and its use for reinforcing concrete is described below.

[0118] Attached Figure 1 An example of a device 10 capable of producing a CPR monofilament according to the invention is schematically shown in a very simple manner.

[0119] The figure shows a reel 11a comprising polyester fibers 11b (in multifilament form) in the example shown. The reel is continuously unwound by a drive, thereby producing a rectilinear arrangement 12 of these fibers 11b. Typically, the reinforcing fibers are delivered as "rovings", i.e. groups of fibers that have been wound in parallel on a reel; for example, a polyester fiber sold by Glanzstoff Longlaville under the name "1X50-3340-892-00" is used, which has a count equal to 334 tex (as a reminder, 1 tex = 1 g / 1000 m of fiber). For example, the traction applied by the rotating receiver 26 will cause the fibers to advance in parallel and the CPR monofilaments to advance along the entire length of the device 1.

[0120] The arrangement 12 is then passed through a vacuum chamber 13 (connected to a vacuum pump (not shown)) arranged between an inlet pipe 13a and an outlet pipe 13b leading to an impregnation chamber 14, the two pipes preferably having rigid walls, for example having a minimum cross-section that is larger than the total cross-section of the fibers (typically twice as large) and a length that is much larger than the minimum cross-section (typically 50 times as large).

[0121] As already taught in the above-mentioned patent application EP-A-1174250, the use of tubes with rigid walls for the inlet to the vacuum chamber and the outlet from the vacuum chamber and for the transfer from the vacuum chamber to the impregnation chamber has proven to be compatible with a high rate of fiber throughput through the opening without breaking the fibers and also to ensure adequate sealing. Taking into account the rate of advancement of the fibers and the length of the tube, it is necessary (if experimentally necessary) to find the maximum flow cross section that still allows adequate sealing, taking into account the total cross section of the fibers to be treated. Typically, the vacuum in the chamber 13 is, for example, about 0.1 bar and the length of the vacuum chamber is about 1 meter.

[0122] On leaving the vacuum chamber 13 and the outlet pipe 13b, the arrangement 12 of fibers 11b passes through an impregnation chamber 14 comprising a feeding tank 15 connected to a metering pump (not shown) and a sealed impregnation tank 16 completely filled with an impregnation composition 17 based on a curable resin of the vinyl ester type (e.g. " E-Nova FW2045"). As an example, the composition 17 also contains (in a weight content of 1% to 2%) a photoinitiator suitable for UV irradiation and / or UV-visible irradiation, for example bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide ("Omnirad 819" from the company IGM), which is subsequently treated with the composition. It can also contain (for example about 5% to 15%) a crosslinker, for example tris(2-hydroxyethyl)isocyanurate triacrylate ("SR 368" from the company Sartomer). Of course, the impregnation composition 17 is in a liquid state.

[0123] Preferably, the impregnation chamber is several meters long, for example between 2 m and 10 m, in particular between 3 m and 5 m.

[0124] Thus, a prepreg comprising, for example (in wt. %) 65 to 75% solid fibres 11 b and the remainder (25 to 35%) formed by a liquid impregnation matrix 17 leaves the impregnation chamber 14 in a sealed outlet pipe 18 (still under rough vacuum).

[0125] The prepreg is then passed through a shaping device 19 comprising at least one shaping die 20, whose channel (not shown here) is, for example, circular, rectangular or even conical, adapted to the specific implementation conditions. As an example, the channel has a circular minimum cross section, the diameter of its downstream orifice being slightly greater than the diameter of the target monofilament. The length of the die is generally at least 100 times the minimum dimension of the minimum cross section. Its purpose is to give the finished product a good dimensional accuracy, and it can also be used to meter the fiber content relative to the resin. According to a possible embodiment variant, the die 20 can be incorporated directly into the impregnation chamber 14, so that, for example, the outlet pipe 18 is not required.

[0126] Preferably, the shaped area is several centimeters long, for example a length between 5 cm and 50 cm, in particular between 5 cm and 20 cm.

[0127] By means of the shaping devices (19, 20), a "liquid" composite monofilament 21 is obtained (liquid in the sense that its impregnation resin is still liquid), the cross-sectional shape of which is preferably substantially circular.

[0128] Then, at the outlet of the shaping device (19, 20), the liquid composite monofilament 21 obtained in this way is polymerized by passing through a UV irradiation chamber (22) comprising a sealed glass tube (23) through which the composite monofilament travels; the tube, which is generally a few centimeters in diameter (for example 2 to 3 cm), is irradiated by a plurality (here for example four) of UV irradiators (24) arranged in a row at a short distance (a few centimeters) from the glass tube (from Dr. "UVAprint" lamp with a wavelength of 200nm to 600nm).

[0129] Preferably, the irradiation chamber is several meters long, for example between 2m and 15m in length, in particular between 3m and 10m in length.

[0130] In this example, the irradiation tube (23) has a nitrogen gas flow flowing through the irradiation tube (23).

[0131] The irradiation conditions are preferably adjusted so that in the irradiation chamber the temperature of the CPR monofilament measured at its surface (eg by a thermocouple) is greater than the Tg of the crosslinked resin (in other words greater than 190°C) and more preferably less than 270°C.

[0132] After the resin polymerizes (cures), the CPR filament (25), now in a solid state and travelling in the direction of arrow F, then reaches its final take-up drum (26).

[0133] Finally, if Figure 2 Very simply shown, the finished composite material body manufactured is obtained in the form of a continuous very long CPR monofilament (25) whose individual polyester threads (251) are evenly distributed throughout the volume of the solidified resin (252). Its diameter is for example equal to about 0.5 mm.

[0134] Due to the above operating conditions, the process of the present invention can be carried out at a high speed greater than 50 m / min, preferably between 50 m / min and 150 m / min, more preferably in the range of 60 m / min to 120 m / min.

[0135] The continuous CPR monofilament (25) may be cut to a given length ( 100 mm) by any method known to those skilled in the art, such as using a hydraulic shear (e.g., "SH-5214" from Baileigh). Figure 1 The length of the monofilament is preferably 45 mm (not shown), for example 45 mm. This step can be performed directly at the exit of the irradiation chamber (23). It can also be performed after the monofilament is packaged on the final take-up drum (26). In this case, it is preferred to unwind the monofilament from the end of the monofilament that is most axially toward the outside of the drum, so as to avoid spiral deformation of the monofilament. Specifically, if the monofilament is unwound from the end of the monofilament that is most axially toward the inside of the drum, this will cause the monofilament to be spirally deformed, which will be unfavorable for the breaking stress.

[0136] IV - Examples

[0137] IV-1 Measurements and tests used

[0138] The porosity was measured according to the following protocol:

[0139] - Obtain cross-linked CPR monofilaments,

[0140] - coating it with a cold coating resin of epoxy type in a vacuum coating device (CitoVac from the company Stuers),

[0141] - cutting the adhesive-coated CPR monofilaments using a hydraulic shear (SH-5214 from the company Baileigh),

[0142] - polishing of the cross-section of the CPR monofilament to a final particle surface of 0.25 μm using a mechanical polisher from the company Mecapol,

[0143] -Using a gold sputtering coater (from the company 108 or 208 series Cressington coater) applies 1nm to 4nm of gold,

[0144] - Observation of cross sections of CPR monofilaments using a scanning electron microscope (15 kV) under vacuum, and

[0145] - Calculate the percentage surface area of ​​pores (% porosity = area of ​​pores / (area of ​​pores + area of ​​fibers + area of ​​cross-linked resin)) using an image processing program (eg FIJI).

[0146] According to standard ASTM D2343, the tensile strength of the CPR monofilaments coated with adhesive (i.e. ready for use) was measured at a temperature of 23°C using an "INSTRON" model 5944 tensile tester (supplied with the tensile tester). UNIVERSAL software) to measure the tensile mechanical properties of CPR monofilaments (modulus E23 , breaking stress Cr and breaking elongation Ar). Before the measurement, these monofilaments were subjected to pre-conditioning (storing the monofilaments for at least 24 hours in a standard atmosphere according to European standard DIN EN 20139 (temperature of 23°C ± 2°C; relative humidity of 50% ± 5%)). In order to prevent damage to the polyester reinforcement when the sample is clamped in the jaws of the tensile tester, the end pieces are connected as follows (material: cardboard, 50 mm long; adhesive used: Loctite EA 9483 (two-component epoxy resin)). The surfaces of the two opposing end pieces are coated with adhesive, as are the reinforcements, thereby limiting any "dry areas" (areas without adhesive) as much as possible. The end pieces are kept in an appropriate position in a fixture with the specimen size for the curing time (12h at 23°C), with weights on the end pieces to ensure good end piece / reinforcement contact. The tensile modulus is determined by linear regression of the stress versus strain curve (between 0.1% strain and 0.6% strain). The strain is recorded by an extensometer MultiXtens 1995DA801. The 260 mm specimens tested were pulled at a nominal speed of 5 m / min under a preload of 0.5 MPa before the test (reference length 50 mm, distance between jaws: 150 mm). All results given are the average of 5 measurements.

[0147] IV-2 Testing of Monofilaments

[0148] CPR monofilaments (M1 and M2) were manufactured according to the above method, wherein the running speed V of the monofilament in the irradiation chamber was ir is 100m / min, and the irradiation time of the monofilament in the irradiation chamber is D ir The irradiation chamber was 2.4 s and the length of the irradiation chamber was 4 m. The resin composition used was based on a vinyl ester resin ("ATLAC E-NOVA FW2045" from the company), a triacrylate hardener ("SR 368" from the company Sartomer) and a photoinitiator ("Omnirad 819" from the company IGM). The polyester threads of the monofilaments M1 and M2 were "1X50-3340-892-00" threads from Glanzstoff Longlaville, respectively. Table 1 below shows the diameter and tex of the monofilaments and their physical and mechanical properties.

[0149] [Table 1]

[0150]

[0151]

[0152] The porosity and breaking stress of these monofilaments are compared with prior art reinforcing fibers for concrete. It is observed that these prior art fibers systematically have a porosity greater than 2% and a breaking stress less than or equal to 300 MPa.

[0153] Due to the low porosity and high breaking stress, the monofilaments of the invention are able to improve the crack resistance of concrete.

[0154] Thus, it was found that the monofilaments according to the invention offer an improved compromise of properties between, in particular, mechanical strength, corrosion resistance, processability (in particular dispersion during mixing, processing temperature and maintenance of homogeneity during drying of the concrete).

Claims

1. A polyester-resin composite monofilament comprising a polyester filament embedded in a cross-linked resin, having a length in the range of 5 mm to 85 mm and a diameter in the range of 0.2 mm to 1.3 mm, characterized in that The porosity of the monofilaments is less than 2%.

2. The monofilament according to claim 1, having a length in the range of 10 mm to 80 mm and having a diameter in the range of 0.25 mm to 1.25 mm, preferably 0.3 mm to 1.2 mm.

3. The monofilament according to any one of the preceding claims, having a length / diameter ratio in the range of 10 to 110, preferably 20 to 90, more preferably 25 to less than 80.

4. The monofilament according to any one of the preceding claims, wherein The polyester filaments account for 20 to 60 wt %, preferably 25 to 40 wt %, of the monofilament, and the cross-linking resin accounts for 40 to 80 wt %, preferably 60 to 75 wt %, of the monofilament.

5. The monofilament according to any one of the preceding claims, wherein The average diameter of each of the polyester filaments is in the range of 15 μm to 35 μm, more preferably 15 μm to 25 μm.

6. The monofilament according to any one of the preceding claims, wherein The cross-linked resin is based on at least: - a crosslinkable resin selected from the group consisting of vinyl ester resins, epoxy resins, polyester resins and mixtures thereof, - a cross-linking system comprising a photoinitiator, which is reactive to UV radiation above 300 nm.

7. The monofilament according to any one of the preceding claims, wherein The polyester thread is a thread selected from polyethylene terephthalate and polyethylene naphthalate, and preferably the polyester thread is completely made of polyethylene terephthalate.

8. Monofilament according to any of the preceding claims, having a porosity of less than 1%, preferably less than 0.5%.

9. Monofilament according to any one of the preceding claims, having a breaking stress greater than 300 MPa, preferably greater than or equal to 320 MPa.

10. The monofilament according to any one of the preceding claims, wherein The monofilament measured at 23°C is denoted as E 23 The initial tensile modulus is greater than 4 GPa, preferably greater than 4.5 GPa.

11. Use of at least one monofilament according to any one of claims 1 to 10 for reinforcing concrete and / or reducing the weight of concrete and / or reducing or preventing cracking of concrete.

12. Concrete comprising a plurality of monofilaments according to any one of claims 1 to 10, wherein the volume ratio of the monofilaments in the concrete is preferably in the range of 0.1% to 6%.

13. A method for producing a polyester-resin composite monofilament according to any one of claims 1 to 10, the polyester-resin composite monofilament comprising a polyester filament embedded in a cross-linked resin, the method comprising the following consecutive steps: - forming a linear arrangement of polyester filaments and conveying this arrangement in the feed direction, - degassing the polyester threads of the arrangement by the action of a vacuum in a vacuum chamber, - at the outlet of the vacuum chamber, after degassing, passing through an impregnation chamber under vacuum to impregnate the arranged polyester threads with a photocurable resin composition called "impregnation resin" in a liquid state, thereby obtaining a prepreg comprising the polyester threads and the resin composition, - passing the prepreg through a shaping die having a cross-section with a predetermined area and shape so as to give it a monofilament shape, - Downstream of the die, the resin composition is polymerized under the action of ultraviolet rays in a UV irradiation chamber, the irradiation chamber comprising a tube transparent to ultraviolet rays, called an irradiation tube, through which the monofilaments to be formed are passed and through which a stream of inert gas flows, the running speed of the monofilaments through the irradiation chamber (denoted by V ir ) is greater than 50m / min, the irradiation time of the monofilament in the irradiation chamber (expressed as D ir ) is equal to or greater than 1.5s, - The monofilaments are cut into lengths ranging from 5 mm to 85 mm.

14. The method according to claim 13, characterized in that The diameter of the monofilaments ranges from 0.2 mm to 1.3 mm, preferably from 0.25 mm to 1.25 mm, preferably from 0.3 mm to 1.2 mm.

15. The method according to any one of claims 13 and 14, wherein: The polyester thread is a thread selected from polyethylene terephthalate and polyethylene naphthalate, and preferably the polyester thread is completely made of polyethylene terephthalate.

Citation Information

Patent Citations

  • Method for manufacturing highly stressed composite pieces

    EP1074369A1

  • Continuous resin impregnation of very long fibres for the manufacturing of elongated composite elements

    EP1174250A1